Electoral Finance and Ecological Governance: A Theoretical Framework for Institutional Constraint in Resource-Dependent Democracies - Imam Hanafi; Vidian Ade Mauludi; Eva Hany Fanida (The Journal of Indonesia Sustainable Development Planning, 2026)
Contemporary electoral systems in resource-dependent countries face a key problem: elections can produce policies that harm the environment. This creates a tension between democratic legitimacy and ecological sustainability. This study explains how electoral finance influences ecological outcomes by developing the Ecological Constraint–Democratic Subordination (ECDS) framework. It addresses a gap in existing research, which often separates campaign finance from environmental governance. The study uses a qualitative comparative case study of Indonesia, Brazil, and the Philippines. The findings show that electoral finance shapes political incentives, which influence policy decisions through three mechanisms: regulatory forbearance, policy favoritism, and institutional capacity reduction. These processes contribute to environmental degradation across contexts. This study provides a framework that links political finance to environmental governance and shows the need to consider political and institutional factors in addressing environmental problems.